Perceptions about climate change among university students in Bangladesh - Haq, Shah Md Atiqul; Ahmed, Khandaker Jafor (Natural Hazards, 2020)
openalex: W3041938809 mag: 3041938809
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

How do teachers’ perceptions of climate change vary in terms of importance, causes, impacts and mitigation? A comparative study in Bangladesh - Chowdhury, Mohammed Thanvir Ahmed; Ahmed, Khandaker Jafor; Ahmed, Mahfuzuddin; Haq, Shah Md Atiqul (SN Social Sciences, 2021)
Since climate change education is an integral element in the increasingly urgent global approach to solving the problem of climate change, understanding perceptions of climate change among teachers in different academic institutions could play a significant role in how and to what extent institutions address the need to educate learners on this subject, specifically, and participate in other climate change mitigation strategies, in general. This study, therefore, examines teachers' perceptions of climate change regarding its significance, causes, consequences, and mitigation, through analysis of a self-administered structured questionnaire completed by 95 teachers from public and private educational institutions in the city of Sylhet in Bangladesh. Results from descriptive and inferential statistical analysis show that public and private school teachers have an understanding of climate change regarding its significance, causes, consequences, and mitigation. The results also reveal that the sociodemographic characteristics of teachers, as well as academic-related factors, influence their perceptions of climate change. This research concludes that teachers in public institutions have a greater awareness and understanding of climate change than those working in private schools. The research findings have broader implications for further research and policy recommendations and, in particular, draw the attention of the Departments of Education and Disaster Management in Bangladesh or in countries with similar contexts to introduce environmental and disaster education and training opportunities for teachers.
openalex: W3185025178 mag: 3185025178
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes

Teachers' Perceptions About Climate Change: A Comparative Study of Public and Private Schools and Colleges in Bangladesh - Ahmed, Mahfuzuddin; Ahmed, Khandaker Jafor; Chowdhury, Mohammed Thanvir Ahmed; Haq, Shah Md Atiqul (Frontiers in climate, 2022)
This study examines school and college teachers' perceptions about climate change, taking into account academic backgrounds and experiences with the impacts of climate change. The study included 95 teachers from three schools and colleges (two private and one public) in the city of Sylhet, Bangladesh. The results show that most teachers have heard about climate change and understand what it means. Most also perceive that temperatures in Bangladesh are rising or fluctuating and that rainfall is falling or fluctuating. The chi-squared test shows that teachers' perceptions about climate change depend on whether their educational institution is private or public and whether they believe their home locality is at risk of extreme weather events (EWE). Binary and multinomial logistic regressions were used to specifically examine the impact of teachers' academic backgrounds and their previous experiences with extreme weather events on their perceptions about climate change. The results of the binary logistic regression show that educational institution type and the teaching levels (SSC: Secondary School Certificate or HSC: Higher Secondary School Certificate; or both levels) in which the teacher teaches are two significant predictors of teachers' perceptions about temperature change. The multinomial logistic regression analysis of perceptions about changes in precipitation shows that there is a statistically significant effect for factors including type of educational institution, bachelor-level study area, hometown vulnerable to EWEs, and environmental or climate-change-related courses taken.
openalex: W4281687641
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:yes

How do teachers’ perceptions of climate change vary in terms of importance, causes, impacts and mitigation? A comparative study in Bangladesh - Chowdhury, Mohammed Thanvir Ahmed; Ahmed, Khandaker Jafor; Ahmed, Mahfuzuddin; Haq, Shah Md Atiqul (SN Social Sciences, 2021)
Since climate change education is an integral element in the increasingly urgent global approach to solving the problem of climate change, understanding perceptions of climate change among teachers in different academic institutions could play a significant role in how and to what extent institutions address the need to educate learners on this subject, specifically, and participate in other climate change mitigation strategies, in general. This study, therefore, examines teachers' perceptions of climate change regarding its significance, causes, consequences, and mitigation, through analysis of a self-administered structured questionnaire completed by 95 teachers from public and private educational institutions in the city of Sylhet in Bangladesh. Results from descriptive and inferential statistical analysis show that public and private school teachers have an understanding of climate change regarding its significance, causes, consequences, and mitigation. The results also reveal that the sociodemographic characteristics of teachers, as well as academic-related factors, influence their perceptions of climate change. This research concludes that teachers in public institutions have a greater awareness and understanding of climate change than those working in private schools. The research findings have broader implications for further research and policy recommendations and, in particular, draw the attention of the Departments of Education and Disaster Management in Bangladesh or in countries with similar contexts to introduce environmental and disaster education and training opportunities for teachers.
openalex: W3185025178 mag: 3185025178
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:import; openalex:yes